LOCALIZATION OF THE MANDIBULAR FORAMEN ON THE PANORAMIC RADIOGRAPHS - Ansari, Asma Saher; Ahmed, Imtiaz (Journal of Ayub Medical College Abbottabad, 2015)
Background: The mandibular foramen is of particular importance to the dentist and dental specialist as it marks the beginning of the mandibular canal, which transmits inferior alveolar nerve and vessels. The aim of this study was the localization of anteroposterior and superioinferior position of the mandibular foramen on the panoramic radiographs in adolescent and young adult in a selected sample of Pakistani population. Methods: This cross Sectional study was conducted in the Orthodontic department of Dr Ishrat ul ebad khan institute of oral health science, Dow University Karachi. Material comprised 150 panoramic radiographs. The radiographs were traced on a cellophane sheet. Landmarks were marked and measurements from the centre of the mandibular foramen to other landmarks were recorded. All measurements were recorded to the nearest millimetre. Results: The mandibular foramen occupies the posterior portion of middle third on antero-posterior width of mandible. A ratio between the sides of one or almost one indicated bilateral symmetry. Conclusion: The locations of the mandibular foramen occupy the middle third of ramus maintains bilateral symmetry in human mandibles.